Elevação da rentabilidade e produtividade em fundições de alumínio secundário: uma proposta metodológica - Diniz, Adriana Gresielly Fabrini (2007)
The aluminum recycling industry has been growing and demanding adaptations of some management tools to this new segment of the market. Concerning the foundry stage, the management of raw materials is fundamental for the sustainability of this sector, some critical aspects are related to the logistics, availability, costs and quality of secondary sources of aluminum. This management is related to the productivity and profitability of the foundry process, because if has a direct influence in the losses of the process. By researching information concerning the production process of a small industry in the segment of foundry, some data has been acquired, which has aided in the determination of the current organizational scenario in terms of productivity, costs and generation of solid residue. Based on the concept of Cleaner Production, the use of raw materials and the technical and financial possibilities of migration to more complex actions aiming the increase of efficiency of the process have been analyzed. The variables of generation of solid residue, type and quantity of secondary raw material have been used as efficiency indicators. The study was based on 214 productive chains of the ASTM B319.1 blend in an induction oven. Statistical analyses about 11 sources of aluminum indicated correlation with the generation of solid residue in only 2 raw materials. Such result indicated the necessity of analyzing the process in broad terms. Based on the concepts of Cleaner Production, a method has been pointed out in order to identify the levels of managing actions of the process and a procedure of technical and financial analysis for implementing actions of continuous improvement aiming the sustainability of the secondary aluminum foundry sector.